The residential context as source of deprivation: Impacts on the local political culture. Evidence from the East German state Thuringia. (March 2019) - Salomo, Katja
Highlights: Multilevel path model tests if context affects political attitudes via deprivation. Considers seven residential qualities as source for perceived deprivation. Strongest predictors: occupational composition, level of immigration, demographic homogeneity. Residential context thus indirectly increases ethnocentrism, democratic discontent. First evidence that demographic homogeneous contexts affect political attitudes.